2020
DOI: 10.5194/bg-17-5263-2020
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties, sensitivities and robustness of simulated water erosion in an EPIC-based global gridded crop model

Abstract: Abstract. Water erosion on arable land can reduce soil fertility and agricultural productivity. Despite the impact of water erosion on crops, it is typically neglected in global crop yield projections. Furthermore, previous efforts to quantify global water erosion have paid little attention to the effects of field management on the magnitude of water erosion. In this study, we analyse the robustness of simulated water erosion estimates in maize and wheat fields between the years 1980 and 2010 based on daily mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…To set up the model for the topographic conditions of the study region, we tested all of the above erosion equations and found that RUSLE provided the lowest and most realistic soil loss, which is consistent with the findings by Carr et al (2020). We also tested several combinations of exponential coefficients in the RUSLE C ‐factor equation and applied the best‐performing combination as given in Supplementary Material (A4).…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…To set up the model for the topographic conditions of the study region, we tested all of the above erosion equations and found that RUSLE provided the lowest and most realistic soil loss, which is consistent with the findings by Carr et al (2020). We also tested several combinations of exponential coefficients in the RUSLE C ‐factor equation and applied the best‐performing combination as given in Supplementary Material (A4).…”
Section: Methodssupporting
confidence: 85%
“…The calculation of the erosivity factor R depends on the specific erosion equation selected by the user, who can choose from seven equations. While the R ‐factor in the erosion equation USLE and its revisions (RUSLE, RUSLE2) is mainly driven by precipitation intensity, in MUSLE, MUST, and MUSS, it is driven by runoff variables, whereas the Onstad‐Foster equation applies a combination (Carr et al, 2020; Williams, 1995). The K ‐factor is computed based on sand, silt, clay, and organic carbon contents of the top soil horizon at the beginning of each simulation year, using the equation provided in Williams (1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tackling environmental challenges in the Anthropocene requires interdisciplinary thinking. To this end, it is appropriate to consider how monitoring approaches and results in general can also be used to improve model accuracy and efficiency (Batista et al, 2019;Carr et al, 2020;Evans and Brazier, 2005). Through building a platform for sharing data and a criterion to increase reproducibility and transparency, our paper (Benaud et al, 2020) also aspired to be a stepping stone in the evolution of scientific and methodological process in this capacity.…”
Section: Introductionmentioning
confidence: 99%